(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The virtual economy, digital trade and digital banking are actually being utilized by the brand-new technology and the broader international network, particularly internet, inside and outwardly. Increasing use of internet, digital gadgets and authorities’ initiative including virtual India with a imaginative and prescient to remodelling India into virtual society via way of means of cashless transaction. After demonetization in India the virtual charge device emerged tremendously. In latest days many modifications happened withinside the charge device like virtual wallets, UPI, AEPS, QR code and BHIM apps for clean shift to virtual payments. The look at investigates a customer`s belief toward Digital payments. The based questionnaire turned into used as studies device for information client belief of virtual charge. Primary statistics turned into amassed from respondents in Chittoor district.